Relative Efficacy of Glue and Other Traps for Commensal Rodent Management - Tripathi, R S; Mathur, Manju; Jain, A P; Patel, Nisha (Annals of Arid Zone, 2016)
Glue, wonder and sherman traps were evaluated against commensal rodent pests (Rattus rattus and Mus musculus) in houses, godowns and poult!)' farms in and around Jodhpur. Sherman trap, being single catch type trap, rated lowest in comparison to multiple catch type traps. Among multiple catch traps, glue traps evidently exhibited an edge over, wonder traps. Ethological manifestations of rodents towards these traps are also discussed.